Startup hiring through firm‐driven search: Evidence from Venture for America - Kim, J. Daniel; Pergler, Michael J. (Strategic Management Journal, 2025)
Abstract Research Summary Due to their limited reputation as potential employers, startups struggle to generate interest (e.g., applications) from jobseekers. To help mitigate these frictions, employers can proactively reach out to jobseekers. In this study, we examine the relationship between firm‐driven search and startups' hiring and retention of young workers. Using a unique empirical setting, we find that firm‐driven search is associated with a higher likelihood of hiring. However, candidates sourced through firm‐driven search exhibit greater turnover rates. In exploring the underlying mechanisms, we find suggestive evidence that candidates perceive firm‐driven search as a favored substitute for their search efforts. For employers, startups with lower visibility and pronounced hiring needs are most likely to engage in firm‐driven search, implying that they do so despite the lower retention prospects. Managerial Summary Startups often struggle to attract applicants due to limited visibility and reputation. This study examines “firm‐driven search,” where startups initiate contact with candidates, using data from Venture for America. We find that this proactive approach improves hiring outcomes but increases employee turnover. Why? Candidates are more likely to consider and accept inbound opportunities, which can result in weaker alignment with their interests or goals. Despite the retention risk, startups with urgent hiring needs or limited reputation often adopt this strategy because the immediate benefits outweigh the costs. The takeaway: firm‐driven search is a powerful but double‐edged tool. It helps less‐visible startups compete for talent—but may lead to higher churn. Founders should balance the short‐term gains in hiring against the long‐term costs of employee turnover.